UNCOVERING THE SIDE OF SOCIAL CHANGE; Examining Its Position as a Method of Ijtihad - Nispul Khoiri Khoiri (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
. When the views of jurists place social change as a legal theory, this paper actually places social change as one of the methods of developing Ijtihad as urf, Maqashid al-sharia and others. The existence of social change is important to determine and nullify the law. Here is the difference between theory and method. As a method its role is broader than a theory that manifests itself independently, it is needed even to determine the existence of the law, besides the law has a dependency on social change. There are several reasons for putting social change as a method of developing Ijtihad, namely: Social change becomes a necessity. Social change as a method has been carried out by friends and scholars such as, Umar Ibn Khathtab who is brilliant and controversial friend in performing jIjtihad, Imam Syafii with qaul qadim and qaul jadid, al-Thufi with the concept of maslahah and finally Ibn Qayyim al-Jauziyyah with the rules of his - the rules of social change. Legal experts such as J.N.D Anderson's research and Jhon L. Esposito, concluded that the method generally developed by Islamic reformers in solving legal problems still relies on a partial approach by exploiting the talfiq and superstitious methods. This shows social change into a method for enriching the Ijtihad method. Keywords: Social change, Islamic law, theory and method